Electrotechnologies for extraction from food plants and biomaterials - Vorobiev, Eugene (Springer, 2017)
Recently, the electrotechnologies based on the effects of pulsed electric fields (PEF), such as ohmic heating (OH) and DC electric field, have gained real interest in the field of food processing. These techniques efficiently enhance methods of extraction from food plants and dehydration of biosolids. The PEF and pulsed OH techniques preserve the nutritional, functional, structural and sensory properties of products better than conventional extraction technologies. The electrofiltration and electro-osmotic dewatering can be very effective for the separation of bioproducts and dehydration of food wastes. The book gives an overview the fundamental principles of electrical techniques, electrophysical properties of foods and agricultural products, application of various emerging electrotechnologies for enhancing the solid-liquid separation and drying processes, extraction techniques of pigments, processing methods of different in-plant tissues and biosolids, electro-osmotic dewatering and electrofiltration of biomaterials, recent industrial- scale gains, and other aspects. Each chapter is complementary to other chapters and addresses the latest efforts in the field.